Application of linear and decision tree methods in assessing the influence of meteorological factors and crop on the level of airborne cladosporium spores - Havrylenko, K. V.; Гавриленко, Ксенія В'ячеславівна (My University, 2024)
The article analyses the influence of environmental factors on the concentration of spores of the Cladosporium fungi in the atmospheric air of Zaporizhzhia in 2016-2020. The seasonal characteristics of fungi spores were analysed: total number of spores; the beginning, duration, and end of the season; maximum value in spores/m3 and the day it was recorded; average day; the number of days that was equal to or exceeded the clinical value (3000 spores/m3). The total number of Cladosporium spores in the period from 2016 to 2020 was 552,470 spores/m3. The highest level of spores – 157904 spores/m3 and the highest daily concentration – 5928 spores/m3 were recorded in 2019. In the same year, the number of days that exceeded the clinical threshold was 13. This is the highest number in all 5 years of monitoring. In contrast, the lowest number of spores was counted in 2020. The total number was 30986 spores/m3, and the daily concentration was 1470 spores/m3. The earliest season started in 2020 and lasted the longest – 166 days. The shortest season lasted 145 days in 2016. Forty five parameters were studied, including 42 meteorological parameters (temperature, pressure, temperature and dew point difference, 16 wind directions, 5 meteorological phenomena in 4 different time intervals of 6 hours (00-05, 05-11, 11-17, 17-23), and 3 types of clouds. The other 3 are crop parameters: daily harvested areas of barley, wheat, and sunflower. Linear regression with two regularisation methods (Ridge regression and The lasso) and decision tree methods (Bagging, Random forests, Boosting, BART) were used to investigate the relationship between Cladosporium spore levels and weather conditions and agricultural activity. The cross-validation mean squared error (CV MSE) was determined to determine the best model and assess the importance of the parameters. The best linear model includes 8 parameters (temperature, pressure, westerny wind, humidity, low-level clouds, fog, the area of daily barley and sunflower harvest). The best decision tree is Bagging. The most meaningful parameters are: dew point, temperature, area of daily harvest of barley and sunflower, pressure, west wind). У статті проаналізовано вплив факторів навколишнього середовища на концентрацію спор грибів роду Cladosporium в атмосферному повітрі м. Запоріжжя у 2016-2020 роках. Проаналізовано сезонні характеристики спор грибів: загальна кількість спор; дата початку та кінця сезону; тривалість сезону, максимальна добова кількість спор та день, коли реєструвалась максимальна кількість спор; середній день; кількість днів, коли концентрація спор дорівнювала чи перевищувала порогове значення (3000 спор/м3). Загальна кількість спор за 2016-2020 роки склала 552470 спор\м3. Найбільша кількість спор ‒ 157904 спор/м3 та найвища добова концентрація ‒ 5928 спор/м3 реєструвалась у 2019 році. В цьому ж році, кількість днів, яка перевищувала клінічне порогове значення склала 13 днів. Це найбільша кількість за усі 5 років моніторингу. Натомість, у 2020 році було підраховано найнижчу кількість спор. Загальна кількість склала ‒ 30986 спор/м3, а добова концентрація ‒ 1470 спор/м3. Найраніше, сезон розпочався у 2020 році та тривав найдовше ‒ 166 днів. Найкоротший сезон тривав 145 днів у 2016 році. Було досліджено 45 параметрів, серед яких 42 – метеорологічні параметри (температуру, тиск, різницю температури і точки роси, 16 напрямів вітру, 5 метеофеноменів у 4 різні проміжки часу по 6 годин (00-05, 05-11, 11-17, 17-23), та 3 види хмар. Інші 3 – параметри врожаю: добові площі збору ячменю, пшениці та соняшника. Для дослідження зв’язку рівню спор Cladosporium з погодними умовами та сільськогосподарською активністю було використано лінійну регресію з двома методами регуляризації (Ridge regression and The lasso), а також методи дерев рішень (Bagging, Random forests, Boosting, BART). Було визначено середню квадратичну похибку, отриману шляхом кросвалідації (CV MSE) для визначення кращої моделі і для оцінки важливості параметрів. Найкраща лінійна модель включає в себе 8 параметрів (температура, тиск, західний вітер, вологість, хмари низького рівня, туман, площа добового збору ячменю та соняшнику) Найкраще дерево рішень – Bagging. Найбільш значущі параметри: точка роси, температура, площа добового збору ячменю і соняшника, тиск, західний вітер).
Застосування лінійних методів та методів на основі дерев рішень у оцінці впливу метеорологічних факторів та врожаю на рівень повітряних спор Cladosporium
Keywords: taxonomic groups; micromycetes; fungi; moulds; fungal spores; Cladosporium; meteorological conditions; sunflower; barley; wheat; yield; human health; correlation; regression; таксономічні групи; мікроміцети; гриби; плісняві гриби; спори грибів; метеорологічні умови; соняшник; ячмінь; пшениця; урожайність; здоров’я людини; кореляція; регресія